Direct production of furfural in one-pot fashion from raw biomass using bronsted acidic ionic liquids - Matsagar, Babasaheb M.; Hossain, Shahriar A.; Islam, Tofazzal; Alamri, Hatem R.; Alothman, Zeid A.; Yamauchi, Yusuke; Dhepe, Paresh L.; Wu, Kevin C. W. (Scientific Reports, 2017)
The conversion of raw biomass into C5-sugars and furfural was demonstrated with the one-pot method using Bronsted acidic ionic liquids (BAILs) without any mineral acids or metal halides. Various BAILs were synthesized and characterized using NMR, FT-IR, TGA, and CHNS microanalysis and were used as the catalyst for raw biomass conversion. The remarkably high yield (i.e. 88%) of C5 sugars from bagasse can be obtained using 1-methyl-3(3-sulfopropyl)-imidazolium hydrogen sulfate ([C3SO3HMIM][HSO4]) BAIL catalyst in a water medium. Similarly, the [C3SO3HMIM][HSO4] BAIL also converts the bagasse into furfural with very high yield (73%) in one-pot method using a water/toluene biphasic solvent system.